A method combining SPITC and 18O labeling for simultaneous protein identification and relative quantification. (21st April 2014) - Zhang, Wenlong; Long, Jia; Zhang, Cheng; Cai, Naixuan; Liu, Zhonghua; Wang, Ying; Wang, Xianchun; Chen, Ping; Liang, Songping
<x xml:space="preserve">Abstract</x> The relative quantification and identification of proteins by matrix‐assisted laser desorption ionization time‐of‐flight MS is very important in /MS is very important in protein research and is usually conducted separately. Chemical N‐terminal derivatization with 4‐sulphophenyl isothiocyanate facilitates de novo sequencing analysis and accurate protein identification, while 18O labeling is simple, specific and widely applicable among the isotopic labeling methods used for relative quantification. In the present study, a method combining 4‐sulphophenyl isothiocyanate derivatization with 18O isotopic labeling was established to identify and quantify proteins simultaneously in one experiment. Reaction conditions were first optimized using a standard peptide (fibrin peptide) and tryptic peptides from the model protein (bovine serum albumin). Under the optimized conditions, these two independent labeling steps show good compatibility, and the linear relativity of quantification within the ten times dynamic range was stable as revealed by correlation coefficient analysis (R2 value = 0.998); moreover, precursor peaks in MS/MS spectrum could provide accurate quantitative information, which is usually acquired from MS spectrum, enabling protein identification and quantification in a single MS/MS spectrum. Next, this method was applied to native peptides isolated from spider venoms. As expected, the de novo sequencing results of each peptide matched with the known sequence precisely, and the measured quantitative ratio of each peptide corresponded well with the theoretical ratio. Finally, complex protein mixtures of spider venoms from male and female species with unknown genome information were analyzed. Differentially expressed proteins were successfully identified, and their quantitative information was also accessed. Taken together, this protein identification and quantification method is simple, reliable and efficient, which has a good potential in the exploration of peptides/proteins from species with unknown genome. Copyright © 2014 John Wiley & Sons, Ltd.